Reproductive wastage in small ruminants in tropical Africa - Kasali, O.B.; Mukasa-Mugerwa, E.; Bekele, T.; Njau, B.C. (International Livestock Centre for Africa, 1989)
Causes of reproductive wastage in small ruminants in tropical Africa are highlighted. Pre- and postnatal deaths account for most of the loss. The role of the International Livestock Centre for Africa in collaboration with the National Agricultural Research Systems in overcoming the multiple factors involved in reproductive wastage in small ruminants is outlined.